2006
DOI: 10.1002/chin.200608221
|View full text |Cite
|
Sign up to set email alerts
|

Recent Achievements in the Synthesis and Application of Inorganic Nanoparticles as Lubricant Components

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access the actual ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…[33][34][35] With the rapid development of nanoscience and nanotechnology, nanoparticles have attracted much attention due to their unique properties and promising applications in electronics, photonics, magnetism and tribology. [36][37][38][39] In the eld of tribology, several types of inorganic nanoparticles such as CaO, CuO, ZnO, TiO 2 , lanthanum borate, [40][41][42][43][44][45] etc. have been successfully used as antiwear and extreme pressure lubrication additives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35] With the rapid development of nanoscience and nanotechnology, nanoparticles have attracted much attention due to their unique properties and promising applications in electronics, photonics, magnetism and tribology. [36][37][38][39] In the eld of tribology, several types of inorganic nanoparticles such as CaO, CuO, ZnO, TiO 2 , lanthanum borate, [40][41][42][43][44][45] etc. have been successfully used as antiwear and extreme pressure lubrication additives.…”
Section: Introductionmentioning
confidence: 99%
“…44 Keeping this in mind, many researchers have prepared surface-modied nanoparticles which do not agglomerate, forming relatively much stable dispersions in base oil and nd pronounced application in tribological industries. 45 Capping nanoparticles with the polar organic molecules is a convenient way to stabilize them since the polar group of a capping agent interacts chemically with the surface of nanoparticles and its non-polar long alkyl chain enhances the solubility of nanoparticles in the base oil, thus, improving the tribological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, nanostructured materials have attracted great attention in various research fields because of their special physical and chemical properties. In the field of tribology, the application of nanoparticles as lubricating additives has received considerable attention . Numerous nanoparticles have been investigated as lubricant additive, such as metal oxides, rare earth compounds, metals, metal carbonate, borates and silicon dioxide …”
Section: Introductionmentioning
confidence: 99%
“…However, nanoparticles are easy to aggregate because of their high surface energy. Thus, surface modifications with organic agents are widely used to improve the surface properties of nanoparticles (Bakunin et al, 2005;Liu et al, 1990Liu et al, , 1996Liu and Guo, 2007;Zhang et al, 1998Zhang et al, , 2001Hu et al, 2000;Chen and Liu, 2006). Chen and Liu (2006) synthesized OA capped nanoparticles and found that the existence of the surface-capping layer could effectively prevent the agglomeration and growth of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%